ECO ROBOT / Anantarajoo Selvarajoo ... [et al.] - Selvarajoo, Anantarajoo; Manogaran, Saras; Ragu, Sritharan; Francis Selvam, Nilson; Saggi, R.Shavena (Division of Research and Industry Linkages, 2017)
The project is about management of sustainable environment using robotic system. The lego mind storm robot were used in the prototype project. The first robot will move in the desired track and search for he project is mainly about the replacing fallen or destroy tress and building temperature management using robotic system. The prototype project consists 2 major robots. The first robot will move in desired track and scan for fallen. When there is tree fallen the robot will dispersed seed in that place. Besides that, the robot also attaches with air moisture control system where the surrounding temperature rises it will spray the surrounding with water. It will ensure moderate surrounding wheatear in the place